HUBUNGAN FREKUENSI KONSUMSI MINUMAN MANIS, AKTIVITAS FISIK DAN STRESS TERHADAP GIZI LEBIH DI SMA MARTIA BHAKTI KOTA BEKASI - Rizki Novianty (2021)
Background: The prevalence of overweight among adolescents 16-18 years in Kota Bekasi has increased from 2013 (7,5%) to 2018 (11,28). Overweight among adolescents can be affected by unbalanced energy intake, sugar sweetened beverages consumption, physical activity and stress. Overweight among adolescents will bother academic achievement and cognitive development. The aim of study: To analyse relationship between sugar sweetened beverages, physical activity, and stress with overweight in SMA Martia Bhakti Kota Bekasi. Methode: Based on cross-sectional study with a purposive sampling involved 70 students. The nutritional status was assessed from anthropometry, SSB consumption were collected from FFQ interview, physical activity were collected from IPAQ questionnaire, and stress were collected from PSS-10 questionnaire. Data was analyzed using Spearman Rank and Pearson correlation test. Result: Based on statistical test result, where the test was obtained p value sugar sweetened beverages (p value = 0,000), physical activity (p value = 0,028), and stress (p value = 0,006) with overweight. Value the strength of correlation sugar sweetened beverages ( r = 0,711), physical activity (-0,262), and stress (0,323). Conclusion: In concluse, SSB consumption, physical activity, and stres were associated with overweight at SMA Martia Bhakti Kota Bekasi.